Feasibility of Glutamate and GABA Detection in Pons and Thalamus at 3T and 7T by Proton Magnetic Resonance Spectroscopy - Younis, Samaira; Hougaard, Anders; Christensen, Casper E.; Vestergaard, Mark B.; Petersen, Esben T.; Boer, Vincent O.; Paulson, Olaf B.; Ashina, Messoud; Marsman, Anouk; Larsson, Henrik B. W. (Frontiers in Neuroscience, 2020)
Abstract Glutamate detection in pons and thalamus using proton magnetic resonance spectroscopy (1H-MRS) after an intervention is of interest for studying various brain disorders. However, 1H-MRS in these brain regions is challenging and time-consuming, especially in longitudinal study designs. 1H-MRS of more cortical structures at the ultra-high magnetic field strength of 7T yields an improved spectral output, including separation of the glutamate signal from the glutamine signal, in a shorter and more feasible scan time, as compared to conventional clinical field strengths. For this purpose, we compared the feasibility of 1H-MRS at 3T and 7T in pons and thalamus by applying a longitudinal study design of repeated measures on same day and three separate days at both field strength in five healthy participants. Total 1H-MRS acquisition time was reduced by a factor 3.75 for pons and by a factor 3 for thalamus at 7T as compared to 3T. We found higher spectral signal-to-noise ratio (SNR) (p<0.001), lower linewidth (p=0.001) and lower Cramér-Rao lower bounds (CRLB) (p<0.001) for the combined glutamate and glutamine signal (Glx) in thalamus at 7T as compared to 3T. In pons, CRLB of Glx was lower at 7T (p<0.001), with no differences in SNR or linewidth compared to 3T. Mean within-subject variability of Glx concentration estimates was lower at 7T compared to 3T for both pons and thalamus. At 7T, it was possible to assess glutamate and gamma-aminobutyric acid (GABA) simultaneously in pons and thalamus. In conclusion, 1H-MRS at 7T resulted in improved spectral quality while allowing shorter scan times than at 3T as well as estimation of the pure glutamate signal in pons and thalamus. This opens up the opportunity for multimodal study designs and multiregional subcortical 1H-MRS research. Glutamate and GABA measurement at 7T in pons and thalamus is advantageous for future investigations of excitatory-inhibitory mechanisms in brain disorders.